2019
DOI: 10.3390/su11143987
|View full text |Cite
|
Sign up to set email alerts
|

Personality Types as Moderators of the Acceptance of Information Technologies in Organizations: A Multi-Group Analysis in PLS-SEM

Abstract: This study aims to examine the influence of personality types on the acceptance of information technologies at work. Based on the model of the five dominant personality traits and the unified theory of acceptance and use of technology, 155 users of Enterprise Resource Planning systems were examined in two Chilean organizations. A cluster analysis applied to personality traits identified three different types of personalities. Subsequently, a multi-group analysis in Partial Least Squares of the technology accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…Supported hypotheses H4, H6, H7, H11 and H14 ( Table 7 and Table 8) as well as H15, H16 and H20 (Table 9) proving that connections between RU->BI, SI->BI, EE->PE, UA->EE, RU->FC, EEt->BI, FCt->BI and SIt->BI are moderated by TJP, confirm the first main hypothesis-the type of job position affects the strength of factor's influence on mobile technology acceptance for knowledge transfer. This is convergent with other studies confirming that depending on the type of technology user -expressed by moderators such as: adopter/non-adopter [61], occupation [74], personal interactivity [76], professionals/novices [78], and personality type [77] -the strength of particular determinants on the intention to use technology might vary significantly. The results presented in Table 8 highlight that there are connections that exist only for particular job types:…”
Section: A Theoretical Implicationssupporting
confidence: 86%
See 3 more Smart Citations
“…Supported hypotheses H4, H6, H7, H11 and H14 ( Table 7 and Table 8) as well as H15, H16 and H20 (Table 9) proving that connections between RU->BI, SI->BI, EE->PE, UA->EE, RU->FC, EEt->BI, FCt->BI and SIt->BI are moderated by TJP, confirm the first main hypothesis-the type of job position affects the strength of factor's influence on mobile technology acceptance for knowledge transfer. This is convergent with other studies confirming that depending on the type of technology user -expressed by moderators such as: adopter/non-adopter [61], occupation [74], personal interactivity [76], professionals/novices [78], and personality type [77] -the strength of particular determinants on the intention to use technology might vary significantly. The results presented in Table 8 highlight that there are connections that exist only for particular job types:…”
Section: A Theoretical Implicationssupporting
confidence: 86%
“…Divergent verification results for occupation and employment moderators, highlight that there should exist moderator that would help to explain whether type of professional work impacts on technology acceptance, especially as other related studies exist (Table 1). Wang et al [81] recognized that there are significant differences between social users and silent users, like employees, regarding the influence of computer self-efficacy on perceived security, the perceived ease of use and perceived security on behavioral intentions Such a research result is strengthen in the study of Ramírez-Correa et al [77] which confirmed that personality types moderate intention to use technology. Moreover personal interactivity was positively verified to impact technology acceptance, where the same factors appeared to be more important for high-interactivity users than low-interactivity [76].…”
Section: Related Researchmentioning
confidence: 93%
See 2 more Smart Citations
“…Therefore, we believe that it is necessary to continue in this line of work to increase this percentage. Among the new proposals to explore the adoption of information technologies, the moderation effects associated with personality types be obvious as an alternative, since there is evidence of their effect between performance expectancy and intention to use information technology [58].…”
Section: Discussionmentioning
confidence: 99%